Social Values as the Soul of Progress: Understanding he Synergetic Impact on Economic Development of Jumla - Budha, Ramesh (Journal of Gurubaba, 2025)
Both economic and non-economic elements influence economic development, and social values are a major determinant of economic behavior and results. Through semi structured interviews and focus groups, this study investigates the connection between social values and economic development in rural Nepal, providing qualitative insights into the ways in which social and cultural factors impact local economies. The results show that gender roles, labor involvement, and financial decisions are significantly influenced by traditional beliefs, customs, and rituals in homes and communities. Cultural customs like marriage ceremonies, religious rites, and neighborhood gatherings have a big impact on how much money is spent and saved, which shapes the economy as a whole. Women are frequently restricted to informal unpaid labor, which limits their economic empowerment. Gender-based norms also have an impact on involvement in productive employment. On the other hand, social values also foster community welfare, solidarity, and collaboration, all of which support sustainable local growth. The study emphasizes that it is impossible to comprehend or accomplish economic growth in rural Nepal without taking into account its cultural context. To achieve equitable and sustainable growth, development programs must acknowledge and incorporate cultural and social values. Depending on their customs, values, and social systems, different cultures have varying degrees of influence. The study's overall goal is to shed light on how social norms and cultural ideas influence economic life by directing productivity, resource allocation, and the larger process of societal advancement.